THE EFFECT OF SELF-EFFICACY, SELF-REGULATED LEARNING, AND STUDENT ENGAGEMENT ON CONCEPT MASTERY OF GRADE XI STUDENTS IN MATHEMATICS LESSONS - Respati Wuryo Putro; Innocentius Bernarto (Lembaga Penelitian Mahasiswa Penalaran UNM, 2024)
Improving the quality of education in Indonesia must be a top priority in building superior human resources. With superior resources, Indonesia can compete in the international world. For that, we need superior resources and mastery of modern technology. Schools and teachers must become Agents of Change to shape young people with professional competence. Therefore, learning in the classroom must be directed so that students can master the concepts of the provided material. In addition, teachers need to improve students' self-confidence and their ability to manage themselves so that students are always actively involved in learning. This study aims to determine how the concept mastery of class XI students at SMA XYZ Jakarta is influenced by self-efficacy, self-regulated learning, and student engagement. This study's respondents were 94 students of class XI SMA XYZ Jakarta. Data was collected using a Google form containing 26 statement items using a Likert Scale. The data were analyzed using SmartPLS 4.0 with an outer and inner model. The research hypothesis is enough to examine whether the path coefficient sign is by the hypothesis. The results of the study show that self-efficacy, self-regulated learning, and student engagement have a positive effect on concept mastery.